Simultaneous degradation of tetracycline and denitrification by magnetic biochar biocathode system: Performance, pathways, and mechanisms - Yanmei Lu; Yuelong Qin; Ziqi Li; Xiaolan Zhou; Zeming Wu; Yi Zhang; Jiaqing Nie; Bing Qiu (Journal of Water Process Engineering, 2026)

Enhancing source-level DC component of AC triboelectric nanogenerator via mirror asymmetry mechanism - Zhaojuan Shi; Sheng Zhang; Menghe Gao; Wenxuan Li; Yinxi Da; Zeming Guo; Jianjun Li; Qiang Tang; Cheng Xu (Chemical Engineering Journal, 2026)

Functional differences between healthy and stressed soils: Rare and abundant root exudates as a regulatory switch for quorum sensing in rhizosphere microbiota - Yueyi Liu; Zhenchao Wu; Zeming Ye; Liangyang Mao; Xiujun Tu; Yuhao Guo; Weige Yao; Ying Yang; Shuo Li; Jie Kang; Baiyan Cai; Jingping Ge (Plant and Soil, 2026)

Battling PFAS: Microbial frontlines and removal mechanisms in constructed wetlands - Yaoxuan Cheng; Jiacheng Shang; Xuanrui Liu; Zeming Shi; Xinyue Zhao; Lixin Li (Journal of Environmental Chemical Engineering, 2026)

Endoplasmic reticulum stress mediates oxidative stress-driven endothelial impairment and atherogenesis induced by sodium perfluorononenoxybenzene sulfonate exposure - Boxiang Zhang; Zeming Liu; Qing Li; Mingming Tian; Yue Gao; Hiroko Kishi; Dan Xu (Environmental Research, 2026)

LncRNA TUG1 promotes hypertrophic scar formation via the miR-627/IGF1R axis - Zeming Bai; Ziyang Han; Xiangzi Kong; Rirui Zhao; Haiwei Sun; Hai Huang; GuYue Wang; Zhe Li; Kai Tao; Jiulong Liang (Journal of Molecular Histology, 2026)
Hypertrophic scars (HS) are fibrotic skin disorders driven by abnormal fibroblast activity. The molecular mechanisms underlying HS remain incompletely understood, particularly the role of non-coding RNAs. Expression levels of lncRNA TUG1, miR-627, and IGF1R were measured in HS tissues and fibroblasts using qRT-PCR and Western blotting. Dual-luciferase assays validated direct interactions. Functional effects of TUG1 and miR-627 on fibroblast proliferation and migration were assessed using MTT and Transwell assays. A rabbit ear model of HS was used to examine in vivo effects of TUG1 and miR-627 modulation on scar formation and molecular expression. TUG1 was significantly upregulated in HS tissues and inversely correlated with miR-627, which was downregulated. TUG1 promoted fibroblast proliferation and migration by directly sponging miR-627, thereby lifting repression on IGF1R, a known pro-fibrotic effector. Luciferase assays confirmed direct binding of miR-627 to both TUG1 and IGF1R. Co-transfection of miR-627 attenuated TUG1-induced IGF1R upregulation and reversed its pro-fibrotic cellular effects. In vivo, TUG1 overexpression led to increased scar thickness, collagen deposition, and IGF1R expression, while miR-627 overexpression mitigated these effects. Co-administration of both restored scar morphology and molecular markers to near-control levels. TUG1 promotes hypertrophic scar formation by sponging miR-627 and derepressing IGF1R. This newly identified TUG1–miR-627–IGF1R axis plays a central role in HS pathogenesis and may serve as a promising therapeutic target for fibrotic skin disease.

Causal Transformer for Learning Embeddings from Structured Medical History Records and Multi-Source Data Integration for Complex Disease Risk Prediction - Zeming Li; Yu Xu; Debajyoti Chowdhury; Hip Fung Yip; Chonghao Wang; Lu Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2026)
Traditional disease risk prediction models predominantly rely on statistical algorithms and often focus on genetic factors or a limited set of lifestyle factors to estimate the risk of disease onset. Recently, more comprehensive approaches have emerged that integrate genetic factors with additional lifestyle factors (e.g., alcohol intake) and physical features (e.g., body mass index, age) to increase predictive accuracy. Since the onset of complex diseases is often accompanied by the occurrence of comorbidities, incorporating medical history records is a critical yet underexplored avenue for improving risk prediction. In this study, we propose a novel framework, MIDRP (Multi-source Integration for Disease Risk Prediction), which incorporates genetic variants, lifestyle factors, physical attributes, and medical history records to achieve more robust and accurate predictions. At the heart of our approach lies a causal Transformer architecture, specifically designed to extract and interpret nuanced patterns from medical history records. In the experiments, we compared MIDRP with several baselines, including LDPred2, random forest, multilayer perception, logistic regression, AdaBoost, DiseaseCapsule, EIR, and Med-Bert, on three complex diseases Coronary Artery Disease, Type 2 Diabetes, and Breast Cancer using data from the UK Biobank. Our method achieved state-of-the-art performance, AUROC scores of 0.783, 0.841, and 0.784, respectively, demonstrating its potential in the field of complex disease risk prediction.

Study on the pro-inflammatory mechanism mediated by the RANK-SPP1 axis in macrophage immunomodulation during atherosclerosis - Qiyu Sun; Yanbo Hu; Zeming Sun; Mingyan Shang; Zhengyi Li; Juan Shen; Zhenzhen Cui; Jiaxin Yang; Xiaowen Ma; Min Li (Molecular and Cellular Biochemistry, 2026)

SynCom improves carbon fixation capacity in phenanthrene-contaminated soils by reshaping microbial communities - Youai Zhang; Mengyao Wang; Lingyu Zhang; Wenjie Li; Wanting Ling; Zeming Wang; Ahmed Mosa; Yanzheng Gao (Journal of Environmental Management, 2026)

Real-Time Functional Lesion Simulation in Connectomics: Rapid Sensitivity Analysis of Neural Pathways via Traversal Tree-Correlated Cuts - Zeming Li (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Spatio-temporal variations of heavy metal(loid)s and their influencing factors in surface sediments of Daya Bay, South China Sea - Zeming Wang; Nan Zheng; Man Hao; Yahui Xu; Jinmei Li (Frontiers in Marine Science, 2026)
To elucidate the spatiotemporal dynamics and driving mechanisms of heavy metal (loid)s (HMs) in coastal systems, this study investigated the surface sediments from Daya Bay across four seasons. Results indicated that the average HM concentrations (mg/kg) decreased in the order of Zn (65.35) > Pb (28.66) > Cu (13.19) > As (7.06) > Hg (0.073) > Cd (0.058), with Pb, As and Hg exhibiting significant seasonal heterogeneity ( p < 0.05). The Geo-accumulation Index ( I geo ) and Contamination Factor identified Hg as the dominant contaminant, registering the highest average I geo value of 2.039. Overall, the surface sediments in the study area exhibited a moderate level of cumulative pollution with an average Pollution Load Index (PLI) of 2.48, following a seasonal decline of winter (2.76) > spring (2.49) > autumn (2.39) > summer (2.27). Crucially, Redundancy Analysis revealed that the distribution of Cu, Zn, Cd, and Pb was primarily governed by natural physicochemical binding to fine-grained, organic-rich matrices. In contrast, the accumulation of Hg and As exhibited a stronger dependency on dynamic biogeochemical factors, notably dissolved oxygen and anthropogenic nutrient inputs. These findings highlight the necessity of distinct management strategies that account for the coupling between sediment matrices and water column biogeochemistry.

Customizable sub-nanometer vertical-step grayscale lithography - Haonan Ma; Shijie Zhao; Xia Liu; Ziying Hu; Xu Han; Hongtao Li; Zeming Jin; Mingdi Zhang; Jixiang Li; Wenke Fu; Yunyun Dai; Yuan Huang; et al. (Science Bulletin, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Ethanol-induced stable dispersion and compatibility of MXene in WEP leading to highly ordered layered materials for high electromagnetic interference shielding performance - Yingfan Li; Bohan Ding; Xiaoyan Ma; Yongjie Bi; Zeming Jin; Yue Sun; Jinghe Guo; Yanxiang Wang; Chao Teng (Chemical Engineering Journal, 2026)

Microalgae in multipollutant synergistic removal: mechanisms, regulatory networks, and cross-scale integration - Chunlai Song; Zeming Shi; Lixin Li (Rendiconti Lincei. Scienze Fisiche e Naturali, 2026)

Corrigendum to “Microstructure characteristics and corrosion behaviors of Mg alloys under various multiple-passes hot-rolling deformation” [Chem. Eng. J. 524 (2025) 169715] - Yuan Zhang; Zeming Li; Wei Liu; Yun Liu; Liansheng Chen (Chemical Engineering Journal, 2026)

Non-directly bonded single-atom pairs towards H2/CO electrooxidation - Tongtong Yang; Heng Liu; Hengjie Liu; Weiyi Zhao; Jiawei Ge; Wenhui Wang; Shuai Yang; Meijian Tang; Kai Wei; Kangcheng Wang; Zeming Qi; Xian Wang; et al. (Science Bulletin, 2026)

Pathogen-induced H2O2 triggers phosphorylation of the RNA-binding protein RRM2R to suppress OsMAPKKK18 intron retention for orchestrating rice immunity and growth - Xiang Lu; Yibang An; Wenxiu Lu; Jing Li; Qing Xiong; Miaomiao Zhu; Yao He; Jia Yang; Yue Wang; Zeming Zhang; Xiaorong Gong; Yulong Qian; et al. (Molecular Plant, 2026)

Geochemical signature and genesis of heavy metals in soils and sediments from a typical pyrite mining area in Southwestern China - Kai Zhao; Zeming Shi; Yinghai Zhu; Yixin Li; Qi Liu; Qiuyu Huang; Xiaohan Liu (Environmental Geochemistry and Health, 2026)

Contrasting Behavior for Li-Mg Isotopes during Subduction: Insights from Garnet in the Yardoi Schists, Tibet - Xing Li; Yilin Xiao; Olivier Nadeau; Dong-Yong Li; Haiyang Liu; Zeming Zhang; Zhenhui Hou (Journal of Earth Science, 2025)

Microstructure characteristics and corrosion behaviors of Mg alloys under various multiple-passes hot-rolling deformation - Yuan Zhang; Zeming Li; Wei Liu; Yun Liu; Liansheng Chen (Chemical Engineering Journal, 2025)

Heteroaggregation between polystyrene micro(nano)plastics and dibutyl phthalate mediates toxicity reduction in macroalgae: Physiological and transcriptomic evidence from Gracilariopsis lemaneiformis - Yuanxia Li; Xiaoqian Zhang; Nianjun Xu; Mingze Chen; Wenting Tang; Na Zhou; Ting Zeng; Xue Sun; Zeming Zhang (Journal of Hazardous Materials, 2025)

Extremely high toxicity of gaseous intermediate/semi volatile organic compounds emitted from typical incomplete biomass burning in China - Yueqian Wang; Di Wu; Zihua Guo; Xiu Chen; Yang Li; Yifei Tan; Zeming Ye; Yuzhe Liu; Yaoqiang Huo; Qing Li; Jianmin Chen (Journal of Hazardous Materials, 2025)

KC1036, a multi-kinase inhibitor with anti-angiogenic activity, can effectively suppress the tumor growth of Ewing sarcoma - Xuejin Ou; Ge Gao; Qizhi Ma; Diyuan Qin; Kai Li; Mingyang Feng; Yu Gao; Yao Zeng; Yue Chen; Xia He; Ting Zhang; Zeming Mo; et al. (Angiogenesis, 2025)

Development and swallowability evaluation of easy-to-swallow anthocyanin-loaded ROS-responsive hydrogels - Yumeng Wang; Siyi Tang; Meili Xin; Zhiying Li; Guoli Ao; Xu Xie; Yihan Li; Zijing Li; Zeming Wang; Xilin Wu; Jinlong Tian; Bin Li (Innovative Food Science & Emerging Technologies, 2025)

A lightning augmented recurrent nowcasting model based on self-supervised learning and multi-modal fusion method - Liang Zhang; Qian Li; Zeming Zhou; Kangquan Yang (Atmospheric Research, 2025)

Causes and influencing mechanisms of differences in phosphorus occurrence forms in sediments of different types of urban lakes - Yinghai Zhu; Zeming Shi; Qian Li; Chengjie Zou; Na Zhang; Xinyu Wang; Kai Zhao (Science of The Total Environment, 2025)

Effects of dietary rumen-degradable protein on the growth performance, energy, and nitrogen metabolism of dairy buffalo heifers - Qingfeng Tang; Pengcheng Shao; Chongli Wen; Zeming Bu; Guangsheng Qin; Yali Huang; Yuhong Pan; Zhipei Li; Kelong Wei; Shulu Li; Bishi Lan; Huapei Zhong; et al. (Tropical Animal Health and Production, 2025)

Effects of elevated CO2 concentration on Se accumulation and associated rhizobacterial community in Cardamine hupingshanensis - Huawei Zang; Wenyao Shi; Minyi Kau; Jiayuan Li; Jinxing Li; Wanying Zhang; Zeming Zhou; Bowen Sun; Linxi Yuan; Renbin Zhu (Plant and Soil, 2025)

Seasonal and spatial variations of nutrients and environmental effects under anthropogenic influence in Daya Bay, China - Jincheng Zhao; Jiawei He; Cai Li; Zeming Yang; Cong Liu; Xianqing Zhang; Min Qin; Dejing Tang; Wen Zhou; Zhantang Xu; Yuanyue Cheng (Frontiers in Marine Science, 2025)
Nutrients are crucial factors for the growth of phytoplankton, and their biogeochemical processes directly impact marine biodiversity. In this study, based on two cruise observations in spring and summer of 2024, the seasonal and spatial variations of nutrients, chlorophyll a, and other ecological indicators in Daya Bay were explored. The results indicated that the average concentrations of dissolved inorganic nitrogen and silicate were 3.61 ± 3.99 µM and 26.27 ± 13.91 µM in summer, respectively, compared with 2.48 ± 1.53 µM and 23.8 ± 6.77 µM in spring. The average concentration of dissolved inorganic phosphate was 0.29 ± 0.12 µM in summer, lower than 0.32 ± 0.09 µM in spring. The stoichiometric proportion among nutrients at most monitoring stations were far from Redfield ratio, and a succession from N-limited to P-limited was observed. A transformation has been observed in the dominant composition of dissolved inorganic nitrogen, shifting from ammonia to total oxidized nitrogen as the main component, which is mainly attributable to the decrease in aquaculture activities in Daya Bay over the last 3 years. In addition, the warm wastewater discharge from nuclear power stations directly influences the distribution of phytoplankton in the surrounding areas. This study provides timely information regarding recent shifts in ecological indicators and is significant to the ecological protection, environmental management, and policy adjustment in Daya Bay.

Single-cell atlas profiling revealed cellular characteristics and dynamic changes after PD-1 blockade therapy of brain metastases from laryngeal squamous cell carcinoma - Yunzhi Zou; Hao Duan; Zekun Deng; Rong Xiang; Jixiang Zhao; Zhenhua Zhang; Wanming Hu; Yuanzhong Yang; Zeming Yan; Shujuan Wen; Zexian Liu; Gao Zhang; et al. (Molecular and Cellular Biochemistry, 2025)
Brain metastasis (BM) in laryngeal squamous cell carcinoma (LSCC) is uncommon but prognosis is poor. Anti-PD-1 immunotherapy benefits some advanced LSCC cases, yet its efficiency is limited by tumor complexity. We analyzed paired metastatic tumor samples from before and after immunotherapy using single-cell RNA sequencing (scRNA-seq), along with a primary LSCC dataset and bulk RNA sequencing. This identified changes post-immunotherapy and revealed differences in single-cell transcriptomes among LSCC, primBM, and neoBM. Our findings show that anti-PD-1 treatment suppresses metastasis-promoting pathways like VEGF and EMT in cancer cells, and alters immune cell functions. Notably, it upregulates T cell activation, leading to CD8 T cell exhaustion from excess heat shock proteins, notably HSPA8. However, CD8 T cell cytotoxic functions improve post-treatment. In myeloid cells, anti-PD-1 therapy enhances antigen presentation and promotes a proinflammatory shift post-metastasis. Additionally, NUPR1 is linked to BM in LSCC, and NEAT1 is a potential metastatic cancer cell cycle participant. Our study provides insights into cancer heterogeneity and the impact of PD-1 immunotherapy on metastasis, aiding precise diagnosis and prognosis.

Analysis of potential human accumulation differences and mechanisms of environmental new flame retardants: Based on in vitro experiments and theoretical calculations - Junchao Ma; Chao Qin; Juan Yan; Chunyu Wang; Yu Liu; Zeming Wang; Zekai Li; Yanzheng Gao (Science of The Total Environment, 2025)

Mn oxide-modified biochars with high adsorption capacity for Pb(II) in wastewater: Preparation and adsorption mechanisms - Jiabo Wang; Hongxia Zhu; Yue Hu; Laigang Hu; Zeming Wei; Yan Ying Li; Xinglu Hu (Environmental Research, 2025)

The Role of MicroRNA-206 in the Regulation of Diabetic Wound Healing via Hypoxia-Inducible Factor 1-Alpha - Zeming Bai; Dapeng Zhou; Kai Tao; Feng Lin; Hongyi Wang; Haiwei Sun; Ruidi Liu; Zhe Li (Biochemical Genetics, 2025)
Successful wound healing in diabetic patients is hindered by dysregulated miRNA expression. This study aimed to investigate the abnormal expression of miRNAs in diabetic wound healing and the potential therapeutic role of modulating the miR-206/HIF-1α pathway. MicroRNA assays were used to identify differentially expressed miRNAs in diabetic wound sites and adjacent areas. In vitro models and a rat diabetic model were established to evaluate the effects of miR-206 on HIF-1α regulation and wound healing. The study revealed differential expression of miR-206 in diabetic wound tissues, its interaction with HIF-1α, and the inhibitory effect of miR-206 on cell growth under high glucose conditions. Modulating the miR-206/HIF-1α pathway using miR-206 antagomir promoted HIF-1α, CD34, and VEGF expression, ultimately enhancing diabetic wound healing.

Machine learning-based surrogate models for fast impact assessment of a new building on urban local microclimate at design stage - Zeming Zhao; Hangxin Li; Shengwei Wang (Building and Environment, 2024)

A microfluidic analyzer based on liquid waveguide capillary cells for the high-sensitivity determination of phosphate in seawater and its applications - Jincheng Zhao; Zeming Yang; Dejing Tang; Min Qin; Wen Zhou; Cong Liu; Zhantang Xu; Yuanyue Cheng; Xianqing Zhang; Cai Li (Analytica Chimica Acta, 2024)

The crustal structure of southeast Tibet from joint inversion of surface wave dispersion and gravity anomaly data - Haopeng Chen; Ruirui Fan; Nanqiao Du; Feng Bao; Zeming Zhang; Xuelei Li; Fang Zou; Chuang Xu (Journal of Asian Earth Sciences, 2024)

Revisiting Neoproterozoic tectono-magmatic evolution of the northern margin of the Yangtze Block, South China - Peng Wu; Yuan-Bao Wu; Shao-Bing Zhang; Yong-Fei Zheng; Long Li; Ying Gao; Hao Song; Zhengqi Xu; Zeming Shi (Earth-Science Reviews, 2024)

The Arabian Sea and Bay of Bengal play a key role in extreme precipitation during the snow season over the Tibetan Plateau - Weiguo Wang; Hongyi Li; Zeming Xie; Xiaohua Hao; Jian Wang (International Journal of Climatology, 2024)
Water vapour is a critical component of the hydrological cycle and plays a key role in climate systems and water resources on the Tibetan Plateau (TP). However, the effect of water vapour on extreme precipitation during the snow season over the TP, where snow cover is widespread, has not been determined. In this study, we investigated the water vapour contributions from extreme precipitation events during the snow season from 1980 to 2017 in four subregions of the TP using the flexible particle dispersion method. We divided the TP into four regions: the northeastern TP (NETP), northwestern TP (NWTP), southeastern TP (SETP) and southwestern TP (SWTP). The water vapour contributions from extreme precipitation among the four subregions were clearly different. The most important water vapour area that contributed the most water vapour to extreme precipitation over the NETP was from local contributions; nevertheless, Central Asia contributed the most water vapour to the NWTP. Water vapour from the Arabian Sea and Bay of Bengal (ASBB) dominantly controlled extreme precipitation in the SETP at a ratio of 45% and in the SWTP at a ratio of 72.9%. The water vapour contribution from the ASBB was significantly correlated with the extreme precipitation occurring in the TP subregions during the snow season in comparison to that of non‐extreme precipitation. These results could improve the understanding of water vapour cycle differences across the interior TP; additionally, our study provides a theoretical reference for the relationship between the snow distribution and water vapour sources in the TP.

Endowing polymeric carbon nitride photocatalyst with CO2 activation sites by anchoring atomic cobalt cluster - Yaru Shang; Yijie Hou; Xun Cao; Hengjie Liu; Xiaoli Jin; Jiawei Liu; Chunshuang Yan; Yumin Qian; Li Song; Zeming Qi; Pin Song; Yansong Zhou; et al. (Chemical Engineering Journal, 2024)

Mangrove plants are promising bioindicator of coastal atmospheric microplastics pollution - Yuanyin Huang; Ziying Zhu; Tianmu Li; Minqian Li; Zeming Cai; Xiaocui Wang; Han Gong; Muting Yan (Journal of Hazardous Materials, 2024)

Mining subsidence monitoring using distributed scatterers InSAR based on Goldstein filter and Fisher information matrix-weighted optimization - Zeming Tian; Lifeng Zhao; Hongdong Fan; Tao Lin; Tao Li (Natural Hazards, 2024)

Identification of groundwater hydrogeochemistry and the hydraulic connections of aquifers in a complex coal mine - Zeming Hou; Lei Huang; Shengwei Zhang; Xuan Han; Jiang Xu; Yanna Li (Journal of Hydrology, 2024)

Flexural behavior of wet panel-to-panel groove-and-tongue joints provided with lapped U-bars - Ao Dong; Zhenyu Li; Bin Rong; Changxiang Wang; Zeming Wang; Hui Xu (Engineering Structures, 2024)

Combined effects of microplastics and antibiotic-resistant bacteria on Daphnia magna growth and expression of functional genes - Xiaofeng Chen; Xiaocui Wang; Yuanyin Huang; Ziying Zhu; Tianmu Li; Zeming Cai; Minqian Li; Han Gong; Muting Yan (Science of The Total Environment, 2023)

Dietary oregano essential oil supplementation alters meat quality, oxidative stability, and fatty acid profiles of beef cattle - Pengjia He; Yu Lei; Ke Zhang; Rui Zhang; Yunpeng Bai; Zeming Li; Li Jia; Jinping Shi; Qiang Cheng; Yannan Ma; Xiaoqiang Zhang; Lishan Liu; et al. (Meat Science, 2023)

Suppressing hydrogen evolution and eliminating sulfation in lead-carbon batteries via potential-matching g-C3N4@rGO nanosheets - Daiwen Tao; Xiong Liu; Simiao Huang; Zeming Li; Hui Yang; Jinyu Wang; Qilong Zhang (Chemical Engineering Journal, 2023)

Toxic effects of three perfluorinated or polyfluorinated compounds (PFCs) on two strains of freshwater algae: Implications for ecological risk assessments - Liangliang Zhang; Xiaowei Zheng; Xianglin Liu; Jue Li; Yanyao Li; Zeming Wang; Nan Zheng; Xiangrong Wang; Zhengqiu Fan (Journal of Environmental Sciences, 2023)

Geothermal springs with high δ13CCO2-DIC along the Xianshuihe fault, Western Sichuan, China: A geochemical signature of enhanced deep tectonic activity - Jinlong Liang; Yi Yu; Zeming Shi; Zhipeng Li; Yi Huang; Hao Song; Jinyong Xu; Xinyu Wang; Xiaocheng Zhou; Luyu Huang; Zebin Luo; Jue Tong; et al. (Journal of Hydrology, 2023)

Bioinspired rapid self-replenishing liquid-infused surfaces for stable anti-adhesion of electrosurgical electrodes - Zeming Li; Wenshuai Wu; Jiayu Sun; Jiteng Li; Deyuan Zhang (Chemical Engineering Journal, 2023)

Illumination Adaptive Multi-Scale Water Surface Object Detection with Intrinsic Decomposition Augmentation - Zhiguo Zhou; Zeming Li; Jiaen Sun; Limei Xu; Xuehua Zhou (Journal of Marine Science and Engineering, 2023)
Visual object detection is an essential task for the intelligent navigation of an Unmanned Surface Vehicle (USV), which can sense the obstacles while navigating. However, the harsh illumination conditions and large scale variation of the objects significantly harm the performance of object detection methods. To address the above problems, we propose a robust water surface object detection method named multi-scale feature fusion network with intrinsic decomposition generative adversarial network data augmentation (MFFDet-IDGAN). We introduce intrinsic decomposition as data augmentation for the object detection to achieve illumination adapting. And an intrinsic decomposition generative adversarial network (IDGAN) is proposed to achieve unsupervised intrinsic decomposition. Moreover, the multi-scale feature fusion network (MFFDet) adopts an improved bidirectional feature pyramid network (BiFPN) and spatial pyramid pooling (SPP) blocks to fuse features of different resolution for better multi-scale detection. And an improved weighted stochastic weight averaging (SWA) is proposed and applied in the training process to improve the generalization performance. We conduct extensive experiments on the Water Surface Object Detection Dataset (WSODD), and the results show that the proposed method can achieve 44% improvement over the baseline. And we further test our method on a real USV in the sailing process, the results show that our method can exceeding the baseline by 4.5%.

Characterization of modified rice straw biochar in immobilizing Bacillus subtilis 168 and evaluation on its role as a novel agent for zearalenone-removal delivery - Jie Han; Jiao Zhang; Jun Meng; Yuanqi Cai; Mo Cheng; Siyu Wu; Zeming Li (Journal of Hazardous Materials, 2023)

Effect of dissolved organic matter on selective oxidation of toluene by ozone micro-nano bubble water - Zeming Xie; Jiali Shentu; Yuyang Long; Li Lu; Dongsheng Shen; Shengqi Qi (Chemosphere, 2023)

Enhanced oxidation of aromatic hydrocarbons by ozone micro-nano bubble water: Mechanism and influencing factors - Dongsheng Shen; Zeming Xie; Jiali Shentu; Yuyang Long; Li Lu; Lili Li; Shengqi Qi (Journal of Environmental Chemical Engineering, 2023)

Lead single atoms anchored on reduced graphene oxide as multifunctional additive for lead–carbon battery - Daiwen Tao; Xiong Liu; Zeming Li; Hui Yang; Jinyu Wang; Qilong Zhang (Chemical Engineering Journal, 2023)

Acute effects of three surface-modified nanoplastics against Microcystis aeruginosa: Growth, microcystin production, and mechanisms - Xiaowei Zheng; Liangliang Zhang; Chao Jiang; Jue Li; Yanyao Li; Xianglin Liu; Chengwei Li; Zeming Wang; Nan Zheng; Zhengqiu Fan (Science of The Total Environment, 2023)

Microplastic pollution and enrichment of distinct microbiota in sediment of mangrove in Zhujiang River estuary, China - Muting Yan; Xiaofeng Chen; Wei Chu; Weixin Li; Minqian Li; Zeming Cai; Han Gong (Journal of Oceanology and Limnology, 2023)

Ships’ Small Target Detection Based on the CBAM-YOLOX Algorithm - Yuchao Wang; Jingdong Li; Zeming Chen; Chenglong Wang (Journal of Marine Science and Engineering, 2022)
In order to solve the problem of low accuracy of small target detection in traditional target detection algorithms, the YOLOX algorithm combined with Convolutional Block Attention Module (CBAM) is proposed. The algorithm first uses CBAM on the shallow feature map to better focus on small target information, and the Focal loss function is used to regress the confidence of the target to overcome the positive and negative sample imbalance problem of the one-stage target detection algorithm. Finally, the Soft Non-Maximum Suppression (SNMS) algorithm is used for post-processing to solve the problem of missed detection in close range ship target detection. The experimental results show that the average accuracy of the proposed CBAM-YOLOX network target detection is improved by 4.01% and the recall rate is improved by 8.81% compared with the traditional YOLOX network, which verifies the effectiveness of the proposed algorithm.

Phase equilibrium modeling of zircon stability in mantle peridotite: Implication for crust-mantle interaction - Hua Xiang; Jianping Zheng; Yibing Li; Zeming Zhang (Science China Earth Sciences, 2022)

Urban trees in university campus: structure, function, and ecological values - Xueyan Wang; Yanlin Wang; Xiaohan Qu; Bing Huang; Zeming Li; Junjiao Sun; Xiaoqing Wei; Xiuying Yang (Environmental Science and Pollution Research, 2021)

Adsorption-desorption and leaching behaviors of broflanilide in four texturally different agricultural soils from China - Guai Xie; Baotong Li; Limei Tang; Lei Rao; Zeming Dong (Journal of Soils and Sediments, 2021)

Space target detection in optical image sequences for wide-field surveillance - Dan Liu; Xiaodong Wang; Yunhui Li; Zeming Xu; Jianing Wang; Zhonghui Mao (International Journal of Remote Sensing, 2020)

Crystal structure of impurity-free rhodochrosite (MnCO3) and thermal expansion properties - Wen Liang; Lin Li; Rui Li; Yuan Yin; Zeming Li; Xiqiang Liu; Shuangmin Shan; Yu He; Yong Meng; Zengsheng Li; Heping Li (Physics and Chemistry of Minerals, 2020)

Crystal structure of norsethite-type BaMn(CO3)2 and its pressure-induced transition investigated by Raman spectroscopy - Wen Liang; Lin Li; Yuan Yin; Rui Li; Zeming Li; Xiqiang Liu; Chaoshuai Zhao; Shuguang Yang; Yong Meng; Zengsheng Li; Yu He; Heping Li (Physics and Chemistry of Minerals, 2019)

Early Mesozoic magmatism and tectonic evolution of east-central Tibet - Yanfei Chen; Zeming Zhang; Zuolin Tian; Xin Dong; Huixia Ding; Hongchen Mu; Dongyan Kang; Yunshuai Li (International Journal of Earth Sciences, 2018)

Single crystal growth, crystalline structure investigation and high-pressure behavior of impurity-free siderite (FeCO3) - Wen Liang; Yuan Yin; Zeming Li; Rui Li; Lin Li; Yu He; Haini Dong; Zengsheng Li; Shuai Yan; Shuangmeng Zhai; Heping Li (Physics and Chemistry of Minerals, 2018)

High-Temperature Metamorphism, Anataxis and Tectonic Evolution of a Mafic Granulite from the Eastern Himalayan Orogen - Zeming Zhang; Huixia Ding; Xin Dong; Zuolin Tian; Dongyan Kang; Hongchen Mu; Shengkai Qin; Yuanyuan Jiang; Mengmei Li (Journal of Earth Science, 2018)

Single crystal growth, characterization and high-pressure Raman spectroscopy of impurity-free magnesite (MgCO3) - Wen Liang; Zeming Li; Yuan Yin; Rui Li; Lin Chen; Yu He; Haini Dong; Lidong Dai; Heping Li (Physics and Chemistry of Minerals, 2018)

Pressure-dependent Raman spectra of Ba5(PO4)3Cl alforsite - Shuangmeng Zhai; Zeming Li; Sean R. Shieh; Ching-Pao Wang; Weihong Xue (Physics and Chemistry of Minerals, 2018)

Maternal doubled haploid production in interploidy hybridization between Brassica napus and Brassica allooctaploids - Shaohong Fu; Liqin Yin; Mingchao Xu; Yun Li; Maolin Wang; Jin Yang; Tingdong Fu; Jisheng Wang; Jinxiong Shen; Asif Ali; Qiong Zou; Bin Yi; et al. (Planta, 2018)

Mechanism of post-seismic floods after the Wenchuan earthquake in the upper Minjiang River, China - Ding Hairong; Li Yong; Shao Chongjian; Lauvence Svirchev; Xu Qiang; Yan Zhaokun; Yan Liang; Ni Shijun; Shi Zeming (Journal of Earth System Science, 2017)

Detection of inherited mutations for hereditary cancer using target enrichment and next generation sequencing - Yanfang Guan; Hong Hu; Yin Peng; Yuhua Gong; Yuting Yi; Libin Shao; Tengfei Liu; Gairui Li; Rongjiao Wang; Pingping Dai; Yves-Jean Bignon; Zhe Xiao; et al. (Familial Cancer, 2015)

Correlation Between Iodine Intake and Thyroid Disorders: A Cross-Sectional Study from the South of China - Hengqiang Zhao; Yuan Tian; Zeming Liu; Xiaoyu Li; Mengyu Feng; Tao Huang (Biological Trace Element Research, 2014)

Pharmacokinetics of the main compounds absorbed into blood after oral administration of Liu Wei Di Huang Wan, a typical combinatorial intervention of Chinese medical formula - Ning Zhang; Lijing Li; Ping Wang; Hui Sun; Zeming Wu; Chengyu Piao; Xijun Wang (Journal of Natural Medicines, 2013)

Individual and combined effects of MDM2 SNP309 and TP53 Arg72Pro on breast cancer risk: an updated meta-analysis - Hongtao Cheng; Biao Ma; Ran Jiang; Wei Wang; Hui Guo; Na Shen; Dapeng Li; Qunzi Zhao; Rui Wang; Pengfei Yi; Yue Zhao; Zeming Liu; et al. (Molecular Biology Reports, 2012)

Channelized fluids in subducted continental crust: constraints from δD–δ 18 O of quartz and fluid inclusions in quartz veins from the Chinese Continental Scientific Drilling Project - Xiaoming Sun; Li Xu; Weidong Sun; Wei Zhai; Yeheng Liang; Qian Tang; Jinlong Liang; Zeming Zhang; Kun Shen; Fangyue Wang; Mingxing Ling; Robert E. Zartman (International Geology Review, 2011)

Natural and experimental constraints on formation of the continental crust based on niobium–tantalum fractionation - Xing Ding; Craig Lundstrom; Fang Huang; Jie Li; Zeming Zhang; Xiaoming Sun; Jinlong Liang; Weidong Sun (International Geology Review, 2009)